Cry, the beloved country eaudiobook - Paton, Alan (Blackstone Audio, Inc., and Buck 50 Productions, LLC, 2008)
A worldwide best-seller when it was first published in 1948, Alan Paton's impassioned novel about a black man's country under white man's law is a work of searing beauty. Cry, the Beloved Country is the deeply moving story of Stephen Kumalo, a Zulu pastor, and his son, Absalom. Set in the troubled and changing South Africa of the 1940s, it is also the story of a land and a people driven by racial injustice. The book is written with such keen compassion and understanding that the listener shares fully in the gravity of the characters' situations. Paton said of his book: "It is a song of love for one's far distant country." Thus, it is a tale that is passionately African while also being timeless and universal. Ultimately, Cry, the Beloved Country is a work of love and hope, of courage and tragedy, born of the dignity of man.